Acute myeloid leukemia‐induced functional inhibition of healthy CD34+ hematopoietic stem and progenitor cells. (20th May 2021) - Jäger, Paul; Geyh, Stefanie; Twarock, Sören; Cadeddu, Ron‐Patrick; Rabes, Pablo; Koch, Annemarie; Maus, Uwe; Hesper, Tobias; Zilkens, Christoph; Rautenberg, Christina; Bormann, Felix; Köhrer, Karl; et al.
Abstract: Acute myeloid leukemia (AML) is characterized by an expansion of leukemic cells and a simultaneous reduction of normal hematopoietic precursors in the bone marrow (BM) resulting in hematopoietic insufficiency, but the underlying mechanisms are poorly understood in humans. Assuming that leukemic cells functionally inhibit healthy CD34+ hematopoietic stem and progenitor cells (HSPC) via humoral factors, we exposed healthy BM‐derived CD34+ HSPC to cell‐free supernatants derived from AML cell lines as well as from 24 newly diagnosed AML patients. Exposure to AML‐derived supernatants significantly inhibited proliferation, cell cycling, colony formation, and differentiation of healthy CD34+ HSPC. RNA sequencing of healthy CD34+ HSPC after exposure to leukemic conditions revealed a specific signature of genes related to proliferation, cell‐cycle regulation, and differentiation, thereby reflecting their functional inhibition on a molecular level. Experiments with paired patient samples showed that these inhibitory effects are markedly related to the immunomagnetically enriched CD34+ leukemic cell population. Using PCR, ELISA, and RNA sequencing, we detected overexpression of TGFβ1 in leukemic cells on the transcriptional and protein level and, correspondingly, a molecular signature related to TGFβ1 signaling in healthy CD34+ HSPC. This inhibitory effect of TGFβ1 on healthy hematopoiesis was functionally corrobated and could be pharmacologically reverted by SD208, an inhibitor of TGFβ receptor 1 signaling. Overall, these data indicate that leukemic cells induce functional inhibition of healthy CD34+ HSPC, at least in part, through TGFβ1, suggesting that blockage of this pathway may improve hematopoiesis in AML. Abstract : Acute myeloid leukemia (AML)‐induced functional inhibition of healthy CD34+ hematopoietic stem and progenitor cells (HSPC) via secreted factors. In particular transforming growth factor β1 (TGFβ1) plays a role in inhibition of key functions of healthy CD34+ HSPC and blockage of this pathway may serve as therapeutic target to improve hematopoiesis in patients with AML.